A rapid liquid chromatography‐electrospray ionization‐ion mobility spectrometry method for monitoring nine representative metabolites in the seedlings of cucumber and wheat. Issue 3 (10th December 2020) - Lu, Yaling; Wu, Xiangping; Yuan, Lei; Li, Yingdi; Wang, Penghui; Yu, Jianna; Tian, Pingfang; Liu, Wenjie
Abstract: A fast and convenient high‐performance liquid chromatography‐electrospray ionization‐ion mobility spectrometry method was developed to determine nine representative metabolites in the seedlings of cucumber and wheat. The analytical conditions were obtained by optimizing the parameters of high‐performance liquid chromatography and ion mobility spectrometry. Briefly, acetonitrile–0.1% formic acid solution was selected as the mobile phase for gradient elution at a flow velocity of 0.4 mL/min. Under negative electrospray ionization mode, spray voltage of ion mobility spectrometry was 4.5 kV, and drift tube temperature was set at 90°C. The metabolites from seedling leaves were extracted using 80% acetonitrile as the solvent at 4°C for 12 h. Results showed that under soilless culture conditions, the contents of maltose, citric acid, and p‐hydroxybenzoic acid in the seedlings of cucumber and wheat were reduced by low concentration of itaconic acid, succinic acid, and citric acid. Importantly, this analytical approach demonstrated high sensitivity, good linear response, and high selectivity. The lowest limit of detection was 0.004 μg for p‐hydroxybenzoic acid. Overall, this high‐performance liquid chromatography‐electrospray ionization‐ion mobility spectrometry method is sensitive and efficient for rapid separation and identification of plant metabolites.